Reinterpretasi Hadis Eksistensi Wanita di Ranah Politik - Jumrotul Qawwim; Muhammad Alif (Al-Mu'tabar, 2024)
The inequality in the implementation of the roles of men and women due to cultural interpretations of the impression of gender differences will always be a topic of scientific study, including the skeptical attitude towards placing women in the political sphere. One of the factors that strengthens this skepticism is a reflection of the understanding of religious texts, the popular hadith with the paragraph saying that a people will not be lucky if led by a woman. This research is qualitative in nature with a text analysis method based on literature study. The aim is to adapt the understanding of the Koran and hadith regarding the existence of women in the political realm. The results showed that in the re-interpretation of the Qur'an and Hadith it was found that there were several techniques that needed to be mastered textually, contextually and intertextually by testing the reliability of the hadith with the Koran, other valid hadiths, historical facts and relevant scientific truths. The impression of the hadith which prohibits women from taking part in politics can be used as a preventive measure against people who are actually unfit to be leaders in order to minimize harm that will occur and Islam itself does not differentiate between men and women in political rights. The struggle to equalize women's rights in politics should not be seen as fighting against men but rather as normalizing justice in accordance with Islamic principles and sharia in particular. A woman's complete credibility must be prepared when she participates in politics because it concerns the rights of many people.